(i) A ∩ B denotes intersection of the two sets A and B, which consists of elements which are common to both A and B.
Since A ⊂ B, every dement of A is already an element of B.
∵ A ∩ B = A
(ii) A ∪ B denotes the union of the sets A and B which consists of elements which are either in A or B or in both A and B.
Since A ⊂ B, every element of A is already an element of B.
∴ A ∩ B = B
A = {1, 2, 3, 4, 5}
B = {4, 5, 6, 7, 8}
So, A ∪ B = {x : x ϵ A or x ϵ B}
= {1, 2, 3, 4, 5, 6, 7, 8}
A ∪ C = {x : x ϵ A x ϵ C}
= {1, 2, 3, 4, 5, 7, 8, 9, 10, 11}
B ∪ C = {x : x ϵ B or x ϵ C}
= {4, 5, 6, 7, 8, 9, 10, 11}
B ∪ C = {x : x ϵ B or x ϵ D}
= {4, 5, 6, 7, 8, 10, 11, 12, 13, 14}
A ∪ B ∪ C = {x|x ϵ A or x ϵ B or x ϵ C}
= {1, 2, 3, 4, 5, 6, 7, 8, 9, 10,11}
A ∪ B ∪ D = {x : x ϵ A or x ϵ B or x ϵ D}
= {1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14}
B ∪ C ∪ D = {xlx ϵ B or x ϵ C or x ϵ D}
= {4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14}
A ∩(B ∪ C) = all those elements which are common to A and B ∪ C = {xlx ϵ A and x ϵ B ∪ C}
Now, B ∪ C = {4, 5, 6, 7, 8, 9, 10, 11}
∴ A ∩ (B ∪ C) = {1,2,3, 4,5} ∩ {4, 5, 6, 7, 8, 9, 10, 11}
= {4, 5}.
(A ∩ B) ∩ (B ∩ C) = {xlx ϵ (A ∩ B) and x ϵ (B ∩ C)}
Now,
A ∩ B = (xlx ϵ A and x ϵ B}
i.e., elements which are common to A & B
∴ A ∩ B = {1, 2, 3, 4, 5} ∩ {4, 5, 6, 7, 8}
= {4, 5}
Also
B ∩ C = {4, 5, 6, 7, 8} ∩ {7,8, 9, 10,11}
= {7, 8}
Hence, (A ∩ B) ∩ (B ∩ C) = {4, 5} ∩ {7, 8}
= ∮ [∵ there is no element common in {4, 5} and {7, 8}]
(A ∪ D) ∩ (B ∪ C) = {x|x ϵ (A ∪ D) or x ϵ (B ∪ C)}
Now,
A ∪ D = {1, 2, 3, 4, 5,10,11,12,13,14}
and B ∪ C = {4, 5, 6, 7, 8, 9, 10, 11}
∴ (A ∪ D) ∩ (B ∪ C) = {4, 5, 10, 11}
We have,
A = {x : x ϵ N}
= {1, 2, 3,.....}, the set of natural numbers
B = {x : x = 2n, x ϵ N}
= {2, 4, 6, 8,....}, the set of even natural numbers
∴ A ∩ B = {x : x ϵ A and x ϵ B}
= {2, 4, 6,.....}
= B [∵B ⊂ A]
We have,
A = {x : x ϵ N}
= {1, 2, 3,....}, the set of natural numbers
C = {x : x = 2n-1, x ϵ N}
= {1, 3, 5,..} , the set of odd natural numbers
A ∩ C = {x : x ϵ A and x ϵ C}
= C [∵C ⊂ A]
We have,
A = {x : x ϵ N}
= {1, 2, 3,...}, the set of natural numbers
and D = {x : x is a prime natural number}
= {2, 3, 5, 7,...}
A ∩ D = {x : x ϵ A and x ϵ D}
=D [∵D ⊂ A]
We have,
B = {x : x = 2n,x ϵ N}
= {2, 4, 6, 8,....}, the set of even natural numbers
and
C = {x: x = 2n-1, x ϵ N}
= {1, 3, 5,...}, the set of odd natural numbers
B ∩ C = {x : x ϵ B and x ϵ C)
= ∮ [∵ B and C are disjoint sets, i.e., have no elements in common]
Here,
B = {x : x = 2n, x ϵ N)
= (2, 4, 6, 8....}, the set of even natural numbers
and D = {x : x is a prime natural number}
= {2, 3, 5, 7,..}
B ∩ D = {x : x ϵ B and x ϵ D}
= {2}
Here,
C = {x : x = 2n-1,x ϵ N}
= {1,3,5,...}, the set of odd natural numbers
and D = {x : x is a prime natural number)
= {2, 3, 5, 7}
C ∩ D = {x : x ϵ C and x ϵ D}
we observe that except, the element 2, every other element in 0 is an odd natural number.
Hence, C ∩ D = D - {2}
= {x ϵ D : x ≠ 2}
We have,
A = {3, 6, 12, 15, 18, 21}
B = {4, 8, 12, 16, 20}
C = {2, 4, 6, 8, 10, 12, 14, 16}
D = {5, 10, 15, 20}
If A and B are two sets, then the set A - B is defined as
A - B = {x ϵ A : x ∉ B}
(i) A - B = {x ϵ A : x ∉ B) = {3, 6, 15, 18, 21}
(ii) A - C = {x ϵ A ϵ C} = {3, 15,18, 21}
(iii) A - D = {x ϵ A : x ∉ D} = {3, 6,12,18, 21}
(iv) B - A = {x ϵ A : x ∉ A} = {4, 8, 16, 20}
(v) C- A = {x ϵ C : x ∉ A} = {2, 4, 8, 10, 14,16}
(vi) D - A = {x ϵ D : x ∉ A} = {5,10 ,20}
(vii) B - C = {x ϵ B : x ∉ C} = {20}
(viii) B - D = (x ϵ B : x ∉ D} = {4, 8,12,16}
(i) U = {1, 2, 3, 4, 5, 6, 7, 8, 9}, A = {1, 2, 3, 4}, B = {2, 4, 6, 8}, C = {3, 4, 5, 6}
By the complement of a set A, which respect to the universal set U, denoted by A' or Ac or U - A, we mean {x ϵ U : x ∉ A}.
Hence, A' = (x ϵ U : x ∉ A} = {5, 6, 7, 8, 9}
(ii) B' = {x ϵ U : x ∉ B} = {1, 3, 5, 7, 9}
(iii) (A ∩ C)' = {x ϵ U : x ∉ A ∩ C}
Now,
A ∩ C = {x : x ϵ A and x ϵ C} = {3,4}
∴ (A ∩ C)' = {1, 2, 5, 6, 7, 8, 9}
(i) U = {1, 2, 3, 4, 5, 6, 7, 8, 9}
B = {2, 3, 5, 8}
B = {2, 3, 5, 7}
We have,
A ∪ B = {x : x ϵ A or x ϵ B}
= {2, 3, 4, 5, 6, 7, 8}
∴ (A ∪ B)' = {x ϵ U : x ∉ A ∪ B}
= {1, 9}
A' = {x ϵ U : x ∉, A}
= {1, 3, 5, 7, 9}
B' = {x ϵ U : x ϵ B}
= {1, 4, 6, 8, 9}
Hence, A' ∩ B' = {1, 9}
Hence, (A ∪ B)' = A' ∩ B' = {1, 9}
(ii) A ∩ B = {x : x ϵ A and x ϵ B}
= {2}
∴ (A ∩ B)' = {x ϵ U : x ∉ A ∩ B}
= {1, 3, 4, 5, 6, 7, 8, 9}
Also ,
A' ∪ B' = {x :x ϵ A' or x ϵ B'}
= {1, 3, 4, 5, 6, 7, 8, 9}
Hence, (A ∩ B)' = A' ∪ B' = {1, 3, 4, 5, 6, 7, 8, 9}